Éowyn and the Biblical Tradition of a Warrior Woman - Filipczak, Dorota (Text Matters: A Journal of Literature, Theory and Culture, 2017)
The article discusses the portrayal of Éowyn in Tolkien’s The Lord of the Rings in the light of the biblical tradition of the warrior woman. The author focuses on the scene in which Éowyn slays the Nazgûl Lord in the battle of the Pelennor Fields with the help of Meriadoc. This event is juxtaposed against the biblical descriptions of female warriors, in particular Jael and Judith. A detailed analysis of passages from the King James Bible and the Douay-Rheims Bible, with which Tolkien was familiar, allows the reader to detect numerous affinities between his vocabulary and imagery, and their biblical antecedents. Filipczak contends that, by defending the body of the dying Théoden, Éowyn defends the whole kingdom; her action can be interpreted in the light of The King’s Two Bodies by Ernst Kantorowicz. Her threat to the Ringraith (“I will smite you if you touch him”) makes use of the verb that can be found in the descriptions of Jael and Judith in the Protestant and Catholic Bibles respectively. Furthermore, Éowyn’s unique position as a mortal woman who achieves the impossible and thus fulfills the prophecy paves the way for a comparison with the Virgin Mary, whose Magnificat contains elements of “a holy-war song” which were suppressed by traditional interpretations. Consequently, the portrayal of Éowyn blends the features of Jael, Judith and Mary with allusions to St. Joan of Arc. Moreover, her act of slaying the Ringraith’s fell beast reinterprets the story of St. George and the dragon. Filipczak argues that Éowyn’s uniqueness is additionally emphasized because she acts out Gandalf’s words from Minas Tirith and sends the Nazgûl Lord into nothingness.